Grown up digital how the net generation is changing your world - Tapscott, Don 1947- (McGraw-Hill, 2009)
Chances are you know a person between the ages of 11 and 30. You've seen them doing five things at once: texting friends, downloading music, uploading videos, watching a movie on a two-inch screen, and doing who-knows-what on Facebook or MySpace. They're the first generation to have literally grown up digital--and they're part of a global cultural phenomenon that's here to stay. The bottom line is this: if you understand the Net Generation, you will understand the future. If you're a Baby Boomer or Gen-Xer this is your field guide. A fascinating inside look at the Net Generation, this book is inspired by a USDUSD4 million private research study. The author has surveyed more than 11,000 young people. Instead of a bunch of spoiled "screenagers" with short attention spans and zero social skills, he discovered a remarkably bright community which has developed revolutionary new ways of thinking, interacting, working, and socializing. This work also reveals: how the brain of the Net Generation processes information, seven ways to attract and engage young talent in the workforce, seven guidelines for educators to tap the Net Gen potential, parenting 2.0: there's no place like the new home, Citizen Net: How young people and the Internet are transforming democracy. Today's young people are using technology in ways you could never imagine. Instead of passively watching television, the "Net Geners" are actively participating in the distribution of entertainment and information. For the first time in history, youth are the authorities on something really important. And they're changing every aspect of our society, from the workplace to the marketplace, from the classroom to the living room, from the voting booth to the Oval Office